Tracing the Shift in Turkey's Normative Approach towards the International Order through Debates in the UN - (:unkn) unknown (My University, 2014)
0

The normative turn associated with the post-Cold War order has been influential in rising states increasing reference to normative issues like justice and fairness. Rising powers are expected to challenge the established institutions or at least attempt to revise the dominant norms of the system in order to reflect their own interests and values. This paper tentatively treats Turkey as a rising state and attempts to understand the gradual normative shift in Turkey s approach towards international order in the context of Turkey-UN relations over the last decade. To this aim, Turkey s normative approach towards the international order will be comparatively analyzed through the debates at the UN focusing specifically on two consecutive periods, the 1990s and the 2000s. By doing that, the paper will theoretically question and empirically analyze the extent to which Turkey took a revisionist or integrationist posture towards the international order in the UN platform over the last decade.
Keywords: Uluslararası İlişkiler